Potential of Aromatic Plant-Derived Essential Oils for the Control of Foodborne Bacteria and Antibiotic Resistance in Animal Production: A Review - Lianhua Zhang; Fei Gao; Junwei Ge; Hui Li; Fei Xia; Hongtong Bai; Xiangshu Piao; Lei Shi (MDPI AG, 2022)
Antibiotic resistance has become a severe public threat to human health worldwide. Supplementing antibiotic growth promoters (AGPs) at subtherapeutic levels has been a commonly applied method to improve the production performance of livestock and poultry, but the misuse of antibiotics in animal production plays a major role in the antibiotic resistance crisis and foodborne disease outbreaks. The addition of AGPs to improve production performance in livestock and poultry has been prohibited in some countries, including Europe, the United States and China. Moreover, cross-resistance could result in the development of multidrug resistant bacteria and limit therapeutic options for human and animal health. Therefore, finding alternatives to antibiotics to maintain the efficiency of livestock production and reduce the risk of foodborne disease outbreaks is beneficial to human health and the sustainable development of animal husbandry. Essential oils (EOs) and their individual compounds derived from aromatic plants are becoming increasingly popular as potential antibiotic alternatives for animal production based on their antibacterial properties. This paper reviews recent studies in the application of EOs in animal production for the control of foodborne pathogens, summarizes their molecular modes of action to increase the susceptibility of antibiotic-resistant bacteria, and provides a promising role for the application of nanoencapsulated EOs in animal production to control bacteria and overcome antibiotic resistance.